Influencia de la participación de los adultos mayores en su rol de empoderamiento familiar en el CAM – La Esperanza – Essalud 2018. - Tolentino Muedas, Ysela Mercedes (2018)
The research of the thesis entitled "INFLUENCE OF THE PARTICIPATION OF OLDER ADULTS IN THEIR ROLE OF FAMILY EMPOWERMENT IN CAM - LA ESPERANZA - ESSALUD 2018" arises from the need to analyze the influence of the participation of older adults in their role of family empowerment, in this research, 45 CAM users participate, who are over 60 years old and actively participate in the activities carried out in the center. In this investigation, the methods used were the inductive - deductive, ethnographic and statistical method; the techniques used were observation, interview, survey and file review; Likewise, the instruments used were the observation register, interview record, questionnaire and written documents. Through this research it is made known about the centers of senior citizens created by Essalud and which are directed by a social worker; where activities aimed at older adults are carried out in order to improve their quality of life through active aging, which is achieved with the active participation of users. Through the results obtained in this research, it can be affirmed that the active participation of older adults of CAM La Esperanza influences their role of family empowerment.